Langfristige Wohnstandortpräferenzen: Schlechte Nachrichten für ländliche Regionen - Uwe Neumann; Christoph M. Schmidt (Wirtschaftsdienst, 2024)
– Increasing urban-rural disparities with regard to housing are receiving considerable attention in the public debate and in regional policy. The article discusses the extent to which microdata from the German Socio-Economic Panel (SOEP) can be used to analyse changes in residential location preferences. The analysis finds that, among various categories of the residential environment, housing in urban peripheral locations and in rural regions has become less attractive in recent decades.
Keywords: C25; R21; R23; 330